Perkembangan Jama’ah Tarekat (Suluk) Naqsabandiyah di Surau Baiturrahman Lubuak Landua Kabupaten Pasaman Barat (1970-2020) - Rahilda Rahima; Abdul Salam (Jurnal Kronologi, 2023)
This research is a study of religious history which is included in the history of the Humanities and Social Sciences which discusses the Development of the Naqsabandiyah Tarekat (Suluk) at Baiturrahman Surau Lubuak Landua in 1970-2020. In this study, researchers examined the background to the emergence of the Naqsabandiyah Order (Suluk) in Lubuak Landua and the development of the Jama'ah which can be seen from 3 developmental categories, namely the development of the number of Jama'ah, the development of the Jama'ah's origin area and the Spread of Tarekat Studies to other Regions. In this study the researchers saw that in the early stages of development the number of congregations was still small. However, in 1970 the number of congregations began to increase when Sheikh Abdul Majid Khalidi became Mursyid. This study aims to determine the background of the development of the Naqsabandiyah Order (Suluk) in Lubuak Landua and the Development of Jama'ah. This type of research is a qualitative research design using historical research methods which consist of: Heuristics, source criticism, interpretation and writing. From the results of the research it can be seen that: (1) Early development of the Naqsabandiyah Order (Suluk) in Lubuak Landua the number of Jama'ah was still small (2) Developments began to be seen when Sheikh Abdul Majid became Mursyid in 1970 when at that time the development of Surau Facilities occurred as a response to the increase The number of jama'ahs, (3) development seen from 3 categories, namely the growth of the number of jama'ahs, the development of the area of origin of the Jama'ah and the spread of Tarekat Studies to other areas,